Hydrochemical and radiometric evaluation of fresh and thermal waters from Araxá city (Minas Gerais, Brazil) - Bonotto, Daniel M. [UNESP] (Springer Nature, 2021)
This paper reports the hydrochemistry and activity concentration of the natural radionuclides 238U, 234U, and 210Po for three compartments of the hydrological/hydrogeological system in Araxá city, Minas Gerais State, Brazil: 1) mineral waters from the prominent springs Dona Beja (DBS) and Andrade Júnior (AJS), occurring at Barreiro area; 2) surface waters from Barreiro area and vicinity; and 3) rainwater. According to the Rule for Mineral Waters in Brazil (Register 7841) for temperature, the DBS water is cold (< 25 °C), while AJS is hypothermal (25–33 °C). The TDS (Total Dissolved Solids) concentration of DBS is low (70 mg/L), but high in AJS (2898 mg/L). The hydrogeochemical facies corresponded to sodium–(bi)carbonate for AJS and sodium/potassium–bicarbonate for DBS. The hydrochemical differences of DBS and AJS waters reflect the distinct characteristics of their respective aquifer systems. The DBS classification for TDS is the same of the Barreiro basin surface waters (mean TDS = 102 mg/L). Such value is somewhat higher than that of the rainwater and surface waters used for human consumption at Araxá city (TDS < 50 mg/L). The dataset reported in this paper indicated that fluoride and barium exceeded the WHO limits proposed in 2011 for drinking water. Among the natural radionuclides analyzed here that offer potential hazards for the human health is 210Po, whose WHO’s limiting value of 100 mBq/L in drinking water was exceeded in rainwater, thus, restricting the use of this resource as a possible supply of drinking water for the local community.
Keywords: Araxá city; Niobium mining; Phosphate fertilizers production; Thermal waters; Water quality